Climate Change Education and Sustainable Learning in Iceland - Rebecca L. Morrison (CV Edujavare Publishing, 2026)
Climate change education and sustainable learning have emerged as critical priorities in Iceland's education system, reflecting both the nation's unique environmental vulnerabilities and its commitment to global sustainability frameworks. This study examines the implementation, evolution, and outcomes of climate change education across Iceland's preschool, compulsory, and upper secondary education levels, drawing upon national curriculum frameworks, teacher survey data, and empirical evidence from institutional practices. Iceland's approach is distinguished by the 2011 National Curriculum Guide that established sustainability as one of six fundamental pillars of education, the GETA (ActionESD) research project's influence on policy development, and the integration of education for sustainability across all school levels following the 2008 financial collapse. The research identifies four critical dimensions: the pillar-based curriculum integration model, the interplay between research and policy in curriculum development, teacher preparedness and professional development challenges, and the tension between policy ambition and classroom implementation. Findings indicate that while Iceland has achieved remarkable success in embedding sustainability into national curriculum frameworks, a significant implementation gap persists, with 92% of teachers reporting that their schools do not teach about climate change and 66.7% believing the curriculum insufficiently addresses climate education. Persistent challenges include teacher confidence gaps, lack of common understanding of ESD across stakeholders, insufficient resources, and the political volatility of sustainability education. The study concludes that Iceland's model offers valuable insights for nations seeking to integrate climate change into education through research-informed policy and pillar-based curriculum design, while highlighting the necessity of sustained investment in teacher professional development, systematic monitoring, and the creation of common understanding across all educational stakeholders.